Quality Assurance of Business Education Programme in Tertiary Institutions in Nigeria - Seyi David; Enilolobo Ganiyat Folashade (IJEBD (International Journal of Entrepreneurship and Business Development), 2023)
Purpose: This paper discussed the concept of business education programme and the need for quality assurance in tertiary institutions. It examined the important roles of NUC, NCCE and TRCN in assuring quality in business education programme in Nigeria. Design/methodology/approach: This paper focused on the underlined heading as follows: objectives of business education, needs for business education ,quality assurance measuring parameters, constraints of quality assurance in business education such as; inadequate funding; staff recruitment; inadequate teaching and learning materials , control measures of quality assurance in business education, current efforts of ensuring quality in business education in Nigeria were discussed. Findings: On this note, it was recommended that Business Education curriculum should be revisited and tailored towards equipping for self-employment, among others. Therefore, cooperation and collaboration among Business Education’s stakeholders are needed in an attempt to achieve the stated objectives in Business Education by providing ample and proper modern facilities in tertiary institutions. Also, accreditation teams should be selected based on their integrity and not who you know, by this institutions will comply to put in place all the needful in order to be accredited. Paper type: Research paper